Valar Morghulis (All Parasocial Men Must Die): Having Nonfictional Responses to a Fictional Character - Westerman, David K (Communication research reports, 2017)
Previous research has found that parasocial relationships mirror actual social relationships. The purpose of this study is to determine how people reacted to the end of a parasocial relationship per a character death, by applying the Kubler-Ross Stages of Grief Model to Twitter reactions after the death of fictional character Jon Snow from the television show Game of Thrones. The applicability is discussed, as are directions for future research.
https://katalog.adlr.link/Record/ai-68-OLC1993419667